The Profesionalism Improvements of Catholic Religious Teachers in Jember - Petrus Amat Sutadi; Suwognyo Widagdo; Muhaimin Dimyati (International Journal of Social Science and Business, 2019)
The quality of teacher, one that can be seen from the professionalism of the teacher. The professionalism of the Catholic religious teachers   in Jember can be measured from four factors, such as: trainings, teaching experience, school facilities and the quality of supervisions. Based on the explanation above, the formulation of the problem in teaching, teaching experience, school facilities and the quality of supervision in improving the professionalism of the Catholic religious teachers in Jember. This study aims to examine whether there are influences from trainings, teaching experience, school facilities and quality of supervision in improving the professionalism of the Catholic religious teachers in Jember. The population of this study was Catholic religious teachers in Jember. In this study, researchers will use total sampling. In this study, the researcher sample samples of 30 Catholic religious teachers as respondents, because this study uses multiple linear regression analysis of SPSS version 16 application. Based on data analysis shows that the training has a dominantly significant effect on the professionalism of the improvement of Catholic religious teachers in Jember. Whereas teaching experience, school facilities and infrastructures. and quality of supervision gives a not-yet-dominantly effective improvement to the professionalism of Catholic religious teachers in Jember.